Empowering Empowering the Muhammadiyah Farmers Community Through Agribusiness Green Entrepreneurship Based on Cavendish Bananas: Pemberdayaan Jama’ah Tani Muhammadiyah Melalui Agribisnis Pisang Cavendish Berbasis Green Entrepreneurship - Anis Shofiyani; Totok Haryanto; Pujiati Utami; Agus Mulyadi Purnawanto; Hadi Pramono (Universitas Muhammadiyah Palembang, 2025)
This community service activity aims to improve the capacity of Jama'ah Tani Muhammadiyah (JATAM) cadres in Kembaran District in managing agribusiness based on local potential, particularly through semi-organic Cavendish banana cultivation. The activity was implemented through participatory training, utilizing an experiential learning approach, which covered banana cultivation techniques, basic agribusiness financial management, and agricultural product marketing strategies. The results of the activity showed significant improvements in three main aspects. Participants' understanding of Cavendish banana cultivation techniques increased by 76.19%, while their farm accounting skills increased by 61.9%. In terms of marketing, participants' understanding increased by 71.43%, supported by training in packaging, branding, and the use of digital media for promotion. Furthermore, this activity fostered an entrepreneurial spirit among the Jamaah Tani Muhammadiyah of the Kembaran District, encouraging them to develop independent businesses based on semi-organic banana cultivation. Overall, this activity demonstrated that a contextual, practical, and locally based training approach can enhance the competency of cadres in agribusiness development. This program not only provided technical skills but also encouraged a mindset transformation from conventional farmers to modern, independent, market-adaptive agribusiness actors. In the future, it is hoped that this activity model can be replicated in other regions to strengthen community-based economic independence.